Risk Management Problems of Microfinance Institutions - Andryushchenko, Galina Ivanovna; Savina, Margarita Vitalievna; Stepanov, Ilya Aleksandrovich; Zaritova, Kristina Gerasimovna; Tanatova, Dina Kabdullinovna (International Journal of Economics and Financial Issues, 2015)
The article presents a study of the status and trends of microfinance development in Russia as a specific kind of transformation of the financial system in the direction of expanding the range of banking services beyond the boundaries of banking proposals, revealed methodological tools for monitoring the provision of microfinance services in the Russian regions, taking into account budgetary support of this relatively new segment of the modern Russian financial system. A special place in the study is given to the issues of financial and non-financial risks non-financial Russian organizations. Proven that microfinance is currently widespread, allowing access to loan funds for small and medium businesses and the public. The methodological foundations, principles and methods of microfinance. Opened on topical issues of financial and non-financial risks of microfinance organizations, as well as main directions of improvement of mechanisms to reduce the financial risks of microfinance organizations. The study basically allow you not only to get a General idea of the degree of saturation of the Russian microfinance services, but also be used in practice as a tool condition monitoring not only the development of microfinance services, but also the development of microfinance business in the Russian regions. Keywords: microfinance institutions, financial risks, non-financial risks, risk management, microfinance, microfinance processes. JEL Classifications: G21, O21